The Grounded Theory Family Tree - Kara L. Vander Linden (Grounded Theory Review: An International Journal)
Grounded theory has a rich history which starts with its co-developers Barney Glaser and Anselm Strauss, each of whom had an impressive research pedigree. Their famous study on death and dying led to the publication of the seminal book Discovery of Grounded Theory. For years they taught cohorts of students grounded theory. These students contributed to the growth of the grounded theory family tree. Glaser started Sociology Press to publish his numerous books on grounded theory. He also founded the Grounded Theory Institute and the Grounded Theory Review, which facilitated the growth of grounded theory, as did his troubleshooting seminars. The Grounded Theory Institute Fellows and the editors and peer reviewers of the Grounded Theory Review have each contributed to the growth of grounded theory.